Análise comparativa do desenvolvimento psicomotor de bebês prematuros e a termo com e sem risco - Bortagarai, Francine Manara (2016)
The present study was subdivided into three studies whose objectives were to investigate the early signs of psychomotor alteration comparing preterm and full term babies with and without psychic risk and to verify the correlation between these variables and socioeconomic, obstetric and psychosocial risk factors. The study 1 was composed of 30 babies who were investigated in two age groups (3 months and 1 day - 4 months and 29 days and 8 months and 1 day - 9 months and 29 days). Yet studies 2 and 3 were made up of the same sample group: 165 babies in the age group corresponding to 3-4 months and 29 days; 130 babies in the age group of 8 - 9 months and 29 days and 102 babies in the range of 11-12 months and 29 days. There were made interviews relative to socioeconomic, psychosocial, obstetric data and relative to the feeding, sleeping and motor routines in all age groups analysed. The instruments used were the Denver II Test for fine and gross motor performance and, the Clinical Indicators of Developmental Risk and PREAUT Signals, to demonstrate psychic risk. The software’s STATISTICA 9.1 and PAW 17.0 were used for the statistics analyses. The results showed that the variable prematurity was not relevant in the differentiation of the groups due to the small number of preterm babies in the sample. There was a negative repercussion of psychic risk on the psychomotor performance of infants with symptoms such as psychomotor instability, inadequate construction of body image and scheme, and not effectuation of imitation and anticipation of maternal gesture. It was also verified correlation between psychic risk and fine and gross motor delay, especially when the PREAUT Signals evaluated the psychic risk. Therefore, it is necessary to take into account, during the evaluation of child development, psychomotor, psychic and also environmental issues, which may be obstacles to this development, so that we can intervene in time to remove them or minimize them, favoring the positive evolution of the baby.